Nurses' Perceptions of Their Relationships with Informal Carers in Institutional Respite Care for Older People - Sirpa Salin; Marja Kaunonen; Päivi Åstedt-Kurki (Nursing Research and Practice)
The purpose of this study was to describe nurses' experiences of their collaboration and relationships with family members in institutional respite care for the elderly. The family has a particularly important role in respite care, which is an extension of care provided at home. However no published studies were found on this subject. The data were collected through qualitative interviews (N=22). Content analysis of the nurses’ descriptions of their collaboration with family members yielded four main categories as follows: (1) conscious ignoring, (2) attempting to understand the family’s situation, (3) hinting at private family matters, and (4) being a friend. The results lend support to earlier findings which emphasize the complexity of relationships between nurses and family carers. A novel finding here is that these relationships may also develop into friendships. Greater emphasis must be placed on primary nursing so that the nurse and informal carer can build up a genuine relationship of trust. If periods of respite care are to help older people and their families to manage independently, it is imperative that nurses have the opportunity to visit their patients at home.